The Effectiveness of Using Crosswords to Improve Critical Thinking Skills in Economics Learning in Class XI Students at SMAN 5 Pekanbaru - Al Rida Miftahul Hayati; Caska Caska; Mujiono Mujiono (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine the effectiveness of using crossword media to improve students' critical thinking skills and to find out the improvement before and after using crossword media. This type of research is experimental research using the One Group Pretest-Posttest research design. In this study, the population was students in class XI IPS 2 at SMAN 5 Pekanbaru for the 2022/2023 school year with a total of 184 students, and the samples were students in class XI IPS 2 at SMAN 5 Pekanbaru for the 2022/2023 academic year with a total of 37 students. educate. Research data collection was carried out by distributing test questions in the form of pretest and posttest with a total of 12 multiple choice questions each. Thus it can be concluded that the use of crossword media is quite effective in learning and there is an increase in the average of students before and after using crossword media.